Helicid Improves Lipopolysaccharide-Induced Apoptosis of C6 Cells by Regulating SH2D5 DNA Methylation via the CytC/Caspase9/Caspase3 Signaling Pathway. (31st January 2022) - Zhang, Yuan; Wang, Mei; Zhang, Xiaotong; Jiang, Zhenyi; Zhang, Yuanxiang; Fu, Xiangjun; Li, Yanna; Cao, Danping; Han, Jun; Tong, Jiucui
Abstract : DNA methylation is reportedly associated with stress responses and depression. Treatment with antidepressants can regulate DNA methylation and, subsequently, gene expression in the hippocampus. Hence, DNA methylation is a potential target for treatment of depression. Screening of high-throughput data of a rat model of chronic unpredictable mild stress revealed relatively low expression of SH2 domain-containing 5 (SH2D5). SH2D5 can be overexpressed by treatment with helicid. Therefore, in order to further explore the role of SH2D5 in depression and whether helicid mediates the DNA methylation of SH2D5 as a potential antidepressant role, SH2D5 was overexpressed in C6 cells as a lipopolysaccharides (LPS)-induced model of depression. The expression levels of Bax, Bcl-2, Bad, and Daxx, and changes to the CytC/caspase9/caspase3 signal pathway were detected by qRT-PCR and Western blot analyses. After treatment with helicid or silencing of SH2D5, the above indices were detected. The results showed that helicid regulated the CytC/caspase9/caspase3 signaling pathway and improved the apoptosis indices of C6 cells through the overexpression of SH2D5. Interestingly, silencing of SH2D5 reversed the effects of helicid on the above indices. Then, in order to study the underlying mechanism, the cells were administered to helicid or 5-aza-2′-deoxycytidine (5-AzaD) and expression of SH2D5 was detected by qRT-PCR and Western blot analyses, while to assess the DNA methylation level of SH2D5 using bisulfite sequencing/PCR. The results showed that SH2D5 was hypermethylated with low expression in LPS-induced C6 cells, which was reversed by helicid and 5-AzaD. These results suggest that helicid may affect the CytC/caspase9/caspase3 apoptosis signaling pathway and improve the apoptosis indices by mediating DNA methylation of SH2D5.